Implementation of open dialogue in Germany: Efforts, challenges, and obstacles - Heumann, Kolja; Kuhlmann, Mira; Böning, Maike; Tülsner, Helene; Pocobello, Raffaella; Ignatyev, Yuriy; Aderhold, Volkmar; von Peter, Sebastian (Frontiers in Psychology, 2023)
Purpose: The Open Dialogue (OD) approach has been implemented in different countries worldwide. OD not only depends on therapeutic principles but also requires a distinct set of structural changes that may impede its full implementation. In Germany, OD is currently practiced in different mental health care settings across the country. Yet, full implementation of OD principles is limited due to the extreme structural and financial fragmentation of the German mental health care system. With this as a background, the aim of this study was to investigate the efforts, challenges and obstacles of OD implementation in Germany. Methods: This article presents the German results from the international HOPEnDialogue survey, supplemented with expert interview data. 38 teams currently providing OD took part in the survey. 16 expert interviews were carried out with stakeholders from various care settings. Survey data were analyzed descriptively and the qualitative data were evaluated using a thematic analysis approach. Results: While having to adapt to the fragmented German health care system, OD has been OD has been mainly implemented from outpatient service providers and stand-alone services. About half of the teams implemented OD under the conditions of cross-sectoral model contracts and, thus, are considerably limited when it comes to OD implementation. Altogether, OD is not implemented to its full extent in each of the institutions surveyed. Similarly, the expert interviews revealed various challenges that mainly relate to the realization of OD’s structural principles, whereas the implementation of its therapeutic benefits remains less affected. However, these challenges have managed to lead to great commitment by single teams and a certain level of implementation of OD-related concepts. Conclusion: OD in Germany can currently only be fully implemented under the cross-sectoral care model contract system that is often temporary, thus significantly hindering its continuous development. Any evaluation of OD’s effectiveness in Germany thus needs to take into account the fragmented nature of the country’s health care system and control for the multiple barriers that impede implementation. Reforms of the German health care system are also urgently needed to create more favorable conditions for the implementation of OD.